Impact of regulatory measures on the approval timelines of advanced therapy medicinal products by the European Medicines Agency - Simonita Alaburde; Justinas Ivaska; Justinas Ivaska; Greta Kaspute; Tatjana Ivaskiene (Frontiers in Medicine, 2025)
IntroductionThe study examines the impact of regulatory tools, including PRIority MEdicines (PRIME) scheme, on the marketing authorization (MA) timeline of advanced therapy medicinal products (ATMPs) approved by the European Medicines Agency (EMA).MethodsA retrospective analysis of EMA-approved ATMPs was conducted using publicly available European public assessment reports. Timelines from submission to approval, regulatory pathways, frequency of scientific advice (SA), and use of supportive mechanisms such as PRIME and Orphan designation were analyzed.ResultsA total of 27 ATMPs were approved in the EU, 52% of which received PRIME designation and 74% held orphan status. PRIME participation was associated with a 42.7% reduction in time to MA (p = 0.001), and orphan designation with a 32.8% reduction (p = 0.021). PRIME-designated products also had fewer and shorter clock stops and more frequent scientific advice interactions.DiscussionThe PRIME scheme facilitates earlier MA by supporting developers in addressing regulatory requirements more efficiently, shortening time to approval by approximately one year. The study underscores the value of early and frequent engagement with regulatory authorities and the need for tailored regulatory frameworks to support smoother approval processes. These insights can help developers better plan and optimize regulatory strategies. By demonstrating the measurable benefits of PRIME, this research supports its continued use to accelerate access for patients with high unmet medical needs.